Participation in practice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Learning Together Through Participatory Extension A guide to an approach developed in Zimbabwe J Hagmann, E Chuma, K Murwira & M Connolly, Agritex-GTZ-IT Zimbabwe, 2000. 59 pp. Free of charge, order No: A-021-E